The Mediation Role of Supply Chain Practices and Logistics Integration on the Effect of Lean Supply Chain Strategy on Operational Performance - Elif Gilanlı; Onur Çetin (Istanbul Business Research)
Supply chain strategy is the determinant of supply chain management (SCM) and product flow efficiency in the market. Lean supply chain strategy (LSCS), which is based on lean practices in production and supply chain, is a strategy that aims to prevent waste and increase efficiency. Although some studies in the literature examine the relationship of many elements of supply chain management with supply chain performance (SCP), and others examine the correlation of many lean manufacturing elements with performance, studies examining the LSCS-SCP relationship is limited. In addition, the number of studies examining the relationship of LSCS with supply chain practices and logistics integration (LI), as well as the number of studies examining LSCS, supply chain practices, LI, and SCP is much more limited. The research aims to examine the effect of LSCS on the supply chain practices which consists of customer relations (CR) and strategic supplier relations (SSR) and the LI as well as, based on these variables, the effect of LSCS on SCP. Data were obtained from 294 companies in the manufacturing sector through questionnaires. A structural equation model, including LSCS, supply chain practices, LI, and SCP, was tested for the first time. In conclusion, the mediating effects of CR, SSR and LI was emphasized to be important in the impact of LSCS on SCP.